2021
DOI: 10.1177/0961203320985214
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity on hydroxychloroquine blood levels in lupus nephritis patients

Abstract: Introduction In 2016 the American Academy of Ophthalmology(2016-AAO) recommended a maximum daily HCQ use of 5.0 mg/kg real body weight(RBW) taking into consideration minimizing eye toxicity. Retinopathy in systemic lupus erythematosus(SLE) patients was recently associated with obesity and this condition is progressively more common in these patients. However, the impact of obesity in HCQ blood levels remains controversial. Objective To determine if the 2016-AAO recommendation based on RBW with and without maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…Prior studies on determinants of HCQ blood concentrations in adult SLE had demonstrated that daily dose per kilogram of HCQ was associated with blood level of the drug 23 , as also observed herein. However, an inverse correlation between HCQ levels and BMI was reported in adult population 24 , similarly to a recent retrospective report in cSLE patients showing that high BMI was significantly associated with low blood HCQ concentrations.…”
Section: Discussionsupporting
confidence: 75%
“…Prior studies on determinants of HCQ blood concentrations in adult SLE had demonstrated that daily dose per kilogram of HCQ was associated with blood level of the drug 23 , as also observed herein. However, an inverse correlation between HCQ levels and BMI was reported in adult population 24 , similarly to a recent retrospective report in cSLE patients showing that high BMI was significantly associated with low blood HCQ concentrations.…”
Section: Discussionsupporting
confidence: 75%
“…In a 2021 study of 108 lupus nephritis patients, Pedrosa et al determined that obese patients were prescribed a lower daily dose of hydroxychloroquine based upon real body weight (4.4 vs. 4.9 mg/kg/day) but interestingly, the median hydroxychloroquine blood level was higher in the obese patients (BMI ≥30 kg/m 2 ) ( P = 0.002). Although they did not collect data on toxicity, the authors hypothesize that obese patients are, therefore, at an increased risk and posit that dosing based on ideal body weight should be considered [29].…”
Section: Obesitymentioning
confidence: 99%
“…The renal impairment populations were taken into consideration because patients accepting HCQ treatment with renal impairment conditions have been reported in several studies to have retinal toxicity [ 36 , 37 ], hypoglycemia [ 38 ], and QT interval prolongation caused by delayed HCQ excretion during the treatment because of reduced renal function [ 39 , 40 ], while the administration of HCQ in patients with renal disease is still not well documented. MO population was included in this research because their body weight will lead to a lower drug plasma level [ 41 ], thus leads to reduced treatment effect. The geriatric and pediatric populations usually have special liver and renal function for drug disposition, indicating their special need for dosing adjustment [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%